A Study of Mystical Connection between Literary Authority and Patriarchal Power in Toni Morrison's Novels: Exploring Toni Morrison's Novels: Unveiling the Mystical Connection Between Literary Authority and Patriarchal Power (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Tony Morrison is a great writer. She is a great writer. They have shown the oppression of women through a perverted society. Tony Morrison has effectively portrayed a male leader in society, showing that only one man can protect the family, one of which describes the woman as a very weak and silent woman, This deformed society is written as a patriarchal society, the purpose in this paper Land exposes the girl oppression expressed by Morrison as patriarchal Tony. The second aspect of patriarchalism is also on casteism which is the collective identity of the female world. The collective identity is built on their collective oppression which is a shared experience. Women's literature is a mixture of autobiography and ideology. The official narrative voice is required to read their texts. The patriarchal abusive husband is frank from patriarchal and racist ideologies. This is why she is making friends in her life. He strangles his twins in his car and runs away from home.